Chemical Analysis of Local Guinea Grass (Megathyrsus maximus Jacq.) and Mombasa Grass (Megathyrsus maximus Jacq cv. Mombasa) Harvested at 30- and 45-day Cutting Intervals as Forage Grass for Ruminants in Leyte, Philippines - Atole, Angelo Francis F.; Compendio, Jade Dhapnee Z.; Posas, Oscar B.; Cuadra, Lijueraj J.; Gacutan, Jr., Manuel D. (Future Science / FSH-PH Publications, 2025)
The study was conducted to compare the proximate analysis of the Guinea grass (Megathyrsus maximus Jacq.) cultivars (i.e., Local Guinea grass; LG, Mombasa grass; MG) harvested at either 30- or 45-day cutting intervals (CI) in Leyte, Philippines. The Guinea grass cultivars were planted in four plots; at 65 days, all grasses were manually harvested by zeroing. Succeeding harvests followed either at 30- or 45-day CI for six months. The treatment combinations were as follows: LG30 (LG, 30-day CI), LG45 (LG, 45-day CI), MG30 (MG, 30-day CI), and MG45 (MG, 45-day CI). LG has significantly higher dry matter (DM; except 4th harvest), OM, and GE contents (3rd and 4th harvests) than MG. In contrast, MG has significantly higher CP (3rd harvest) and ash (except 3rd harvest) contents than LG. Between CI, Guinea grass cultivars harvested at 45-CI have significantly higher DM, ash (2nd harvest), and OM contents than those harvested at a 30-day CI. In contrast, Guinea grass cultivars harvested at 30-day CI have significantly higher CP (3rd harvest) and EE contents (interaction effect at 4th harvest) than those harvested at 45-day CI. MG can be offered for ruminants requiring high CP and ash contents on a grass-based diet, especially when harvested at a 30-day CI. LG can be offered to ruminants requiring a low plane of nutrition.